2008
DOI: 10.5194/angeo-26-467-2008
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal wave coupling of the stratosphere and mesosphere during the major stratospheric warming in 2003/2004

Abstract: Abstract. The coupling of the dynamical regimes in the high-and low-latitude stratosphere and mesosphere during the major SSW in the Arctic winter of 2003/2004 has been studied. The UKMO zonal wind data were used to explore the latitudinal coupling in the stratosphere, while the coupling in the mesosphere was investigated by neutral wind measurements from eleven radars situated at high, highmiddle and tropical latitudes. It was found that the inverse relationship between the variability of the zonal mean flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 38 publications
5
56
0
Order By: Relevance
“…At 42 km altitude level, the maximum peaks at around ∼3.6 day, ∼8 day, ∼15 day, and ∼21-23 day are observed during the winter 2009 for the four IMFs, respectively. These are in agreement with the work of Pancheva et al (2008), the dominating wave periods of ∼22-23, ∼16 day and ∼11 day in the stratospheric heights using the waves with MLS temperatures and MERRA winds can be observed from the table. During SH winter, Dowdy et al (2004) observed a distinct change in the character of the planetary-wave field associated with SSW events.…”
Section: P Kishore Et Al: Planetary Waves In the Upper Stratospheresupporting
confidence: 92%
See 1 more Smart Citation
“…At 42 km altitude level, the maximum peaks at around ∼3.6 day, ∼8 day, ∼15 day, and ∼21-23 day are observed during the winter 2009 for the four IMFs, respectively. These are in agreement with the work of Pancheva et al (2008), the dominating wave periods of ∼22-23, ∼16 day and ∼11 day in the stratospheric heights using the waves with MLS temperatures and MERRA winds can be observed from the table. During SH winter, Dowdy et al (2004) observed a distinct change in the character of the planetary-wave field associated with SSW events.…”
Section: P Kishore Et Al: Planetary Waves In the Upper Stratospheresupporting
confidence: 92%
“…The key mechanism behind the sudden stratospheric warming (SSW), initially proposed by Matsuno (1971) and now widely accepted, relates to the growth of upward propagating transient planetary waves (PWs) and their non-linear interaction with the zonal mean flow. Later, SSWs are reasonably well characterized from observational data sets (Labitzke and Naujokat, 2000;Hoffmann et al, 2002Hoffmann et al, , 2007Venkat Ratnam et al, 2004;Cho et al, 2004;Pancheva et al, 2008) and also through modeling (Newman and Nash, 2004;Manney et al, 2008b).…”
Section: Introductionmentioning
confidence: 92%
“…Sudden stratospheric warmings (SSWs) are much more prevalent in the Arctic than in the Antarctic due to the larger Northern Hemisphere planetary wave forcing (Manney et al, 2005;Pancheva et al, 2008a). An increase in planetary wave activity is noticed prior to the onset of an SSW which preconditions the atmosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Azeem et al (2005) analyzed the 2002 austral winter temperature data at ∼87 km, inferred from South Pole OH(3,1) airglow measurements, and showed that the strong 4-day wave signature seen in the temperature data was associated with the SW event. Radar studies of Espy et al (2005) and Pancheva et al (2008) also have showed similar intensification of planetary waves prior to the onset of the SSW event. Planetary wave amplification in the MLT region prior to the SSW event was also confirmed by radar wind measurements from Antarctica (Mbatha et al, 2009;Dowdy et al, 2007).…”
Section: Introductionmentioning
confidence: 93%